A case report of allergic bronchopulmonary aspergillosis - disease well known but rarely diagnosed - Justyna Emeryk-Maksymiuk; Anna Grzywa-Celińska; Marcelina Makuch (Kazimierz Wielki University, 2018)
Allergic bronchopulmonary aspergillosis (ABPA) is a consequence of hypersensitivity reaction to Aspergillus fumigatus that can chronically colonize the air ways of patients with abnormalities in their airway mucosal defenses, including mucociliary clearance and epithelial cell function, such as patients with bronchial asthma and cystic fibrosis. We present an interesting case of a 62-year-old woman who presented with purulent cough, subfebrile temperature and chest pain. She was ineffectively treated for a month with standard antibiotics and was finally diagnosed with ABPA.